The anatomy of China's export growth - Amiti, Mary 2001- (The World Bank, 2008)
Decomposing China's real export growth, of over 500 percent since 1992, reveals a number of interesting findings. First, China's export structure changed dramatically, with growing export shares in electronics and machinery and a decline in agriculture and apparel. Second, despite the shift into these more sophisticated products, the skill content of China's manufacturing exports remained unchanged, once processing trade is excluded. Third, export growth was accompanied by increasing specialization and was mainly accounted for by high export growth of existing products (the intensive margin) rather than in new varieties (the extensive margin). Fourth, consistent with an increased world supply of existing varieties, China's export prices to the United States fell by an average of 1.5 percent per year between 1997 and 2005, while export prices of these products from the rest of the world to the United States increased by 0.4 percent annually over the same period